How Lucky Can You Get? - Miller, Erica (Wildlife Rehabilitation Bulletin, 2004)
(From the Introduction) When it comes to careers, I figure I’m one of the luckiest people around. September 2004 marks my 15th year of being a full-time wildlife rehabilitator. I consider myself lucky in my career for four reasons. First, I get paid to rehabilitate wildlife! I not only have a job, but I have a job that I feel good about— not many people can say that these days. The second reason I am lucky is that I have had, and continue to have, opportunities to work with some excellent rehabilitators and generally good people. Some of them are veterinarians, some of them are career wildlife rehabilitators, and many of them are volunteers; all of them are doing great things to help wildlife.